A proactive approach for maritime safety policy making for the Gulf of Finland: Seeking best practices. (October 2015) - Haapasaari, Päivi; Helle, Inari; Lehikoinen, Annukka; Lappalainen, Jouni; Kuikka, Sakari
Abstract: A rapid increase in maritime traffic together with challenging navigation conditions and a vulnerable ecosystem has evoked calls for improving maritime safety in the Gulf of Finland, the Baltic Sea. It is suggested that these improvements will be the result of adopting a regionally effective proactive approach to safety policy formulation and management. A proactive approach is grounded on a formal process of identifying, assessing and evaluating accident risks, and adjusting policies or management practices before accidents happen. Currently, maritime safety is globally regulated by internationally agreed prescriptive rules, which are usually revised in reaction to accidents. The proactive Formal Safety Assessment (FSA) is applied to risks common to a ship type or to a particular hazard, when deemed necessary, whereas regional FSA applications are rare. An extensive literature review was conducted in order to examine the opportunities for developing a framework for the GoF for handling regional risks at regional level. Best practices were sought from nuclear safety management and fisheries management, and from a particular case related to maritime risk management. A regional approach that sees maritime safety as a holistic system, and manages it by combining a scientific risk assessment with stakeholder input to identify risks and risk control options, and to evaluate risks is proposed. A regional risk governance framework can improve safety by focusing on actual regional risks, designing tailor-made safety measures to control them, enhancing a positive safety culture in the shipping industry, and by increasing trust among all involved. Highlights: A regional proactive approach to maritime safety is needed in the Gulf of Finland. Best practices are sought from the nuclear, fisheries, and maritime fields. The proposed framework sees maritime safety as a holistic system. The framework requires scientific risk assessment and stakeholder input.